A fresh look at patterns and assumptions in the field of entrepreneurship: What can we learn? - Dushnitsky, Gary; Matusik, Sharon F. (Strategic Entrepreneurship Journal, 2019)
Abstract Research Summary This article invites scholars to reconsider how the evolution of entrepreneurial phenomena affects the underlying theories employed in our field. We highlight three themes affected by changes to the entrepreneurial journey nowadays in a way that can challenge some foundational research in each area. To that end, we engage in a dual conversation; explicitly revisiting extant theories, as well as deliberately seeking out practice insights on how behaviors and actions are changing. This approach provides fertile ground for future work to re‐examine the theoretical assumptions we often take for granted. Such investigation can either provide fresh evidence of the robustness of extant theory, or create new pathways of inquiry. For entrepreneurship scholars who are dedicated to researching innovation and progress in firms and individuals, this is an exciting time to create innovation and progress in our field. Managerial Summary Has the entrepreneurial journey remained unchanged over the past decades? And if there have been substantive changes, what are they? And what are their implications? These are critical questions that talk to entrepreneurship scholars and practitioners alike. The purpose of this article is to encourage a dialogue among and across the two groups. We present dual theory‐practitioner conversations around three points of dialogue; the origin of entrepreneurial opportunity, organizing and scaling, and resource acquisition. In each case, we show that drawing on both the practice and academic community is important in identifying the value of extant theories and frameworks and where there are important opportunities for new frameworks and predictions. We believe that this kind of theory‐practitioner dialogue offers invaluable guidance to further advance our field. A video abstract is available at https://www.youtube.com/watch?v=R7o9Yy-Vtzs .